2021
DOI: 10.1016/j.dib.2021.106883
|View full text |Cite
|
Sign up to set email alerts
|

Data on the uptake of CpG-loaded amino-dextran nanoparticles by antigen-presenting cells

Abstract: Cytosine-phosphate-guanine (CpG) oligonucleotides are commonly-used vaccine adjuvants to promote the activation of antigen-presenting cells (APCs). To mount an effective immune response, CpG needs to be internalized and bind to its endosomal Toll-like receptor 9 (TLR-9) inside the APCs. Using flow cytometry and fluorescence microscopy, this article presents the cellular uptake data of the amino-dextran nanoparticle (aDNP) and aDNP loaded with CpG immobilized on its surface by either electrostatic adsorption or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The in vivo studies have shown that both distribution and elimination of DEX depend on the molecular mass and overall charge of the polymer. Pharmacodynamically, the DEX-DDS have resulted in a prolonged effect, a low toxicity profile and a decreased immunogenicity of bioactive molecules [ 16 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo studies have shown that both distribution and elimination of DEX depend on the molecular mass and overall charge of the polymer. Pharmacodynamically, the DEX-DDS have resulted in a prolonged effect, a low toxicity profile and a decreased immunogenicity of bioactive molecules [ 16 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%